A single-ion conducting hyperbranched polymer as a high performance solid-state electrolyte for lithium ion batteries. Issue 47 (23rd May 2019) - Zhang, Meng; Yu, Songrui; Mai, Yiyong; Zhang, Shaodong; Zhou, Yongfeng
Abstract : "Crown-PEG"-assisted Li + migration in a hyperbranched single-ion polyelectrolyte. Abstract : This communication reports a novel hyperbranched polymer with poly(ethylene glycol)9 segments and carboxylate groups. The combined advantages of single-ion conduction and a hyperbranched structure make the as-prepared polymers very promising as a solid-state polymer electrolyte for lithium ion batteries, by showing high ionic conductivity up to 1.2 × 10 −4 S cm −1 at 85 °C, a high lithium transference number ( t Li + ) of 0.86, and simultaneously, a stable potential window up to 4.8 V versus Li + /Li.